9sinxcosx-7sin^2x=2cos^2x

+1
Ответы (1)
  1. 13 сентября, 20:00
    0
    9sinxcosx - 7sin²x = 2cos²x;

    Разделим на соs²x каждый член равенства:

    9sinxcosx/cos²x - 7sin²x/cos²x = 2cos²x/cos²x;

    Преобразуем:

    9sinx/cosx - 7tg²x = 2;

    9tgx - 7tg²x - 2 = 0;

    7tg²x - 9tgx + 2 = 0;

    Пусть tgx = t, тогда tg²x = t².

    7t² - 9t + 2 = 0;

    D = (-9) ² - 4 * 7 * 2 = 81 - 56 = 25;

    t = (9 + - 5) / 14;

    t1 = 1, t2 = 2/7;

    tgx = 1;

    x1 = arctg1 + pik, k из Z;

    x1 = pi/4 + pik, k из Z;

    tgx = 2/7;

    x2 = arctg2/7 + pik, k из Z;

    Ответ: pi/4 + pik, k из Z; arctg2/7 + pik, k из Z.
Знаешь ответ на этот вопрос?
Новые вопросы по математике